Development and validation of RP-HPLC and RP-UPLC methods for quantification of parathyroid hormones (1-34) in medicinal product formulated with meta-cresol - Shaligram S. Rane; Alkesh Ajameri; Rustom Mody; P. Padmaja (Elsevier, 2012)
Rapid and sensitive reversed phase high performance liquid chromatography (RP-HPLC) and ultra performance liquid chromatography (RP-UPLC) method with UV detection has been developed and validated for quantification of parathyroid hormone (PTH) in presence of meta-cresol as a stabilizer in a pharmaceutical formulation. Chromatography was performed with mobile phase containing 0.1% Trifluoroacetic acid (TFA) in MilliQ water and 0.1% TFA in acetonitrile with gradient program and flow rate at 0.3 mL/min for HPLC and 0.4 mL/min for UPLC. Quantification was accomplished with internal reference standard (qualified against innovator product and National Institute for Biological Standards and Control (NIBSC) standard). The methods were validated for linearity (correlation coefficient=0.99), range, accuracy, precision and robustness. Robustness was confirmed by considering three factors; mobile phase composition, column temperature and flow rate/age of mobile phase.Intermediate precision was confirmed on different equipments, different columns and on different days. The relative standard deviation (RSD) (<2% for RP-HPLC and <1% for UPLC, n=30) indicated a good precision. Retention time was found about 17 min and 2 min by HPLC and UPLC methods, respectively. Both methods are simple, highly sensitive, precise and accurate and have the potential of being useful for routine quality control. Keywords: Parathyroid hormone, Reversed phase high performance liquid chromatography, Ultra performance liquid chromatography, Validation, Meta-cresol